Transplant outcomes in kidney recipients with lupus nephritis, and systematic review. (March 2020) - Kim, J E; Kim, Y C; Min, S-l; Lee, H; Ha, J; Chin, H J; Kim, Y S; Han, S S
Background: Despite improved survival of patients with lupus nephritis (LN), some require kidney transplantation because of progression to end-stage renal disease (ESRD). However, the transplant outcomes of these patients and other recipients have not been thoroughly compared. Methods: In total, 1848 Korean kidney recipients who underwent transplantation from 1998 to 2017 at two tertiary referral centers were evaluated retrospectively. Among them, 28 recipients with LN, and 50 control recipients matched by age, sex, and donor type, were compared with respect to graft and patient survival. We pooled our data with 17 previous cohort studies in which the graft survival of recipients with LN was described in detail. Results: During the median follow-up period of 9.5 years (maximum 21 years), graft failure (GF) occurred in 10.7% and 16.0% of LN and control recipients, respectively. No differences were found in the rates of GF and death-censored graft failure or patient survival between the two groups. The risks of acute T cell-mediated and antibody-mediated rejection were also similar between the two groups. The pooled analysis showed similar 1- and 5-year graft survival rates between LN and control recipients. Conclusions: Kidney transplantation is an acceptable option in patients with concurrent LN and ESRD.